Results from a national survey on COVID‐19‐associated mucormycosis in Germany: 13 patients from six tertiary hospitals. Issue 1 (16th November 2021) - Seidel, Danila; Simon, Michaela; Sprute, Rosanne; Lubnow, Matthias; Evert, Katja; Speer, Claudius; Seeßle, Jessica; Khatamzas, Elham; Merle, Uta; Behrens, Christopher; Blau, Igor Wolfgang; Enghard, Philipp; et al.
Abstract: Background: Most COVID‐19‐associated mucormycosis (CAM) cases are reported from India and neighbouring countries. Anecdotally cases from Europe have been presented. Objective: To estimate the disease burden and describe the clinical presentation of CAM in Germany. Methods: We identified cases through German mycology networks and scientific societies, and collected anonymised clinical information via FungiScope®. Results: We identified 13 CAM cases from six tertiary referral hospitals diagnosed between March 2020 and June 2021. Twelve patients had severe or critical COVID‐19, eleven were mechanically ventilated for a median of 8 days (range 1‐27 days) before diagnosis of CAM. Eleven patients received systemic corticosteroids. Additional underlying medical conditions were reported for all but one patient, five were immunocompromised because of malignancy or organ transplantation, three were diabetic. Eleven patients developed pneumonia. Mortality was 53.8% with a median time from diagnosis of mucormycosis to death of 9 days (range 0–214 days) despite treatment with liposomal amphotericin B and/or isavuconazole in 10 of 13 cases. CAM prevalence amongst hospitalised COVID‐19 patients overall (0.67% and 0.58% in two centres) and those admitted to the intensive care unit (ICU) (1.47%, 1.78% and 0.15% in three centres) was significantly higher compared to non‐COVID‐19 patients ( P  < .001 for respective comparisons). Conclusion: COVID‐19‐associated mucormycosis is rare in Germany, mostly reported in patients with comorbidities and impaired immune system and severe COVID‐19 treated in the ICU with high mortality compared to mainly rhino‐orbito‐cerebral CAM in patients with mild COVID‐19 in India. Risk for CAM is higher in hospitalised COVID‐19 patients than in other patients.